EFFECTIVENESS OF DISTANCE EDUCATION IN HIGHER EDUCATION (Eureka Journal of Education & Learning Technologies, 2026)
Distance education has become one of the most important components of modern higher education systems. The rapid development of digital technologies and internet accessibility has created new opportunities for students and teachers around the world. This article examines the effectiveness of distance education in higher education institutions, its advantages, challenges, and impact on the quality of learning. The study highlights the role of online platforms, virtual communication, and independent learning in improving educational outcomes. In addition, the article discusses the importance of technological infrastructure, student motivation, and teacher competence in ensuring successful distance learning. The findings show that distance education can provide flexible, accessible, and effective learning opportunities when supported by appropriate educational strategies and modern technologies.
Keywords: Distance education, higher education, online learning, digital technologies, educational effectiveness, virtual classrooms, independent learning, e-learning platforms, teaching methods, modern education.